(Sounding) Silence: Dysfluency Mediated Otherwise - Andi Lois Gilker (Tijdschrift voor Mediageschiedenis)
To conceptualise dysfluency as mediated otherwise, I trace a genealogical history from postwar to contemporary sound experimentations. By examining the generative threshold between sound and silence, I build on some key and emerging scholarship on dysfluency, while highlighting the work of stuttering and stammering practitioners Alvin Lucier and Jerome Ellis, whose pieces, I argue, further an anti-ableist media ecology. Although working through dysfluency in differing ways, Lucier and Ellis build on and transform Cagean ‘silence.’ Constellating a conversation, their pieces offer a way of confronting the limit of silence/sound to point instead to a generative threshold in the interstices. On this threshold of sounding otherwise, my analysis of sound practitioners constellates on dysfluent spacetimes, demonstrating what I have come to term a (sounding) silence.